What are people talking about in moral outrage? Communication processes of online firestorms in Japan - Kato, Hiroki (2020)
In the age of the Internet, anonymous online users can form a societal reaction by posting large quantities of critique and insulting comments against (perceived) norm violations on social media. These so-called online firestorms, or Enjō in Japanese, tend to include aggressive behavior against the target. This research aims to reveal the dynamics of Enjō and explores how people communicate with each other in the formation process of Enjō by conducting a comparative case study. This study collects tweets posted in five Enjō cases and compares each case to create conceptual categories of the communication process of Enjō. Results show that the participants of Enjō interact with each other to define the problem of concern through exchange of information. Moreover, it is revealed that there are two types of process in the escalation of Enjō, “social problematization” and “villainization.” In the conclusion, the implications of these findings are discussed.